2020 3rd International Conference on Advanced Communication Technologies and Networking (CommNet) 2020
DOI: 10.1109/commnet49926.2020.9199638
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency comparison of Outphasing and IDP techniques with non-linear power amplifiers

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Nevertheless, in LINC, the two generated signals before the amplification process have very high power, unlike the IDP method where the power of the two signals to be amplified are much lower. We have compared in [20] the energy efficiency between these two methods and we have shown that the performances with IDP technique are better. In [17], we have proposed the IDP method and we have restricted our theoretical analysis to the order = 2.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in LINC, the two generated signals before the amplification process have very high power, unlike the IDP method where the power of the two signals to be amplified are much lower. We have compared in [20] the energy efficiency between these two methods and we have shown that the performances with IDP technique are better. In [17], we have proposed the IDP method and we have restricted our theoretical analysis to the order = 2.…”
Section: Introductionmentioning
confidence: 99%